2007
DOI: 10.1136/bjo.2007.124966
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humor levels of asymmetric dimethylarginine (ADMA) are positively associated with monocyte chemoattractant protein-1 (MCP-1) in patients with uveitis

Abstract: The results demonstrated that aqueous humor levels of ADMA were positively associated with MCP-1 in humans. Our present observations suggest that aqueous humor levels of ADMA may be a novel biomarker of inflammation in uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…ADMA concentrations in the aqueous have also been previously documented by other investigators in diabetes patients 19 and in patients with uveitis, 20,21 and recently in XFS patients. ADMA concentrations in the aqueous have also been previously documented by other investigators in diabetes patients 19 and in patients with uveitis, 20,21 and recently in XFS patients.…”
Section: Discussionsupporting
confidence: 66%
“…ADMA concentrations in the aqueous have also been previously documented by other investigators in diabetes patients 19 and in patients with uveitis, 20,21 and recently in XFS patients. ADMA concentrations in the aqueous have also been previously documented by other investigators in diabetes patients 19 and in patients with uveitis, 20,21 and recently in XFS patients.…”
Section: Discussionsupporting
confidence: 66%
“…Pro‐inflammatory cytokines in the aqueous humour have been studied to explore the risk of filtering bleb scarring, with CCL2 being one among them (Yoshida et al. ; Wang et al. ; Chua et al.…”
Section: Discussionmentioning
confidence: 99%
“…Becker et al have found that treatment with antibodies for ICAM‐1 inhibited leucocyte adhesion and infiltration, but not rolling, in murine EIU 38 . Yoshida et al have found that aqueous humour MCP‐1 levels were significantly higher in infectious or non‐infectious uveitis patients than in controls 39 . MCP‐1 knockout was shown to inhibit the infiltration of ocular inflammatory cells induced by EIU 40 .…”
Section: Discussionmentioning
confidence: 99%
“…38 Yoshida et al have found that aqueous humour MCP-1 levels were significantly higher in infectious or non-infectious uveitis patients than in controls. 39 MCP-1 knockout was shown to inhibit the infiltration of ocular inflammatory cells induced by EIU. 40 TNF-α, which may be stimulated by Toll-like receptor (TLR) signalling or triggered by increased levels of other chemokines, increases uveitis severity.…”
Section: Discussionmentioning
confidence: 99%